2020
DOI: 10.1128/mbio.00903-20
|View full text |Cite
|
Sign up to set email alerts
|

CD4 + T Cell-Mimicking Nanoparticles Broadly Neutralize HIV-1 and Suppress Viral Replication through Autophagy

Abstract: Therapeutic strategies that provide effective and broad‐spectrum neutralization against HIV-1 infection are highly desirable. Here, we investigate the potential of nanoengineered CD4+ T cell membrane-coated nanoparticles (TNP) to neutralize a broad range of HIV-1 strains. TNP displayed outstanding neutralizing breadth and potency; they neutralized all 125 HIV-1-pseudotyped viruses tested, including global subtypes/recombinant forms, and transmitted/founder viruses, with a geometric mean 80% inhibitory concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 78 publications
1
46
0
Order By: Relevance
“…It has been demonstrated that T cell membrane-coated nanoparticles (TNPs) can bind to HIV and neutralize its infectivity ( Fig. 11 ) [ 328 , 329 ]. The formulation took advantage of the CD4 receptor displayed on the T cell surface that HIV uses for docking.…”
Section: Nanotechnology Interventionsmentioning
confidence: 99%
“…It has been demonstrated that T cell membrane-coated nanoparticles (TNPs) can bind to HIV and neutralize its infectivity ( Fig. 11 ) [ 328 , 329 ]. The formulation took advantage of the CD4 receptor displayed on the T cell surface that HIV uses for docking.…”
Section: Nanotechnology Interventionsmentioning
confidence: 99%
“…Membrane coating derived from immune cells usually exhibits advantages of targeting inflammatory microenvironment, cytokines/PAMPs neutralization, blocking infectious events, and so on. Zhang and coworkers adopted CD4 + T cells as membrane donor to coat PLGA NPs, and obtained a nanoengineered CD4 + T cell membrane-coated NP (TNP) with broad-panel activity to 125 HIV-1-pseudotyped viruses [ 113 ]. As a therapeutic agent, TNP can neutralize cell-free HIV-1 and induce autophagy of HIV-1 gp120-expressing cells, thereby doubly hindering the HIV-1 reservoir [ 113 ].…”
Section: Rationality Of Nanoplatforms In Sepsis Managementmentioning
confidence: 99%
“…Zhang and coworkers adopted CD4 + T cells as membrane donor to coat PLGA NPs, and obtained a nanoengineered CD4 + T cell membrane-coated NP (TNP) with broad-panel activity to 125 HIV-1-pseudotyped viruses [ 113 ]. As a therapeutic agent, TNP can neutralize cell-free HIV-1 and induce autophagy of HIV-1 gp120-expressing cells, thereby doubly hindering the HIV-1 reservoir [ 113 ]. Compared with naked NPs, NPs coated with cancer cell-derived membrane show lower distribution in normal tissues and improved accumulation in tumor tissues and hence have been widely used as carriers of imaging agents and/or therapeutic drugs for cancer theranostics [ 105 ].…”
Section: Rationality Of Nanoplatforms In Sepsis Managementmentioning
confidence: 99%
“…[ 85 ] A follow‐up study confirmed that the T cell membrane‐coated nanoparticles could inhibit a wide range of HIV‐1 strains and surprisingly induced autophagy of HIV‐infected cells to suppress viral genome replication but had no effect on uninfected cells. [ 86 ] Recently, cell membrane‐coated nanoparticles have also been developed to inhibit SARS‐CoV‐2 infection of Vero E6 cells in vitro (Figure 5d). [ 84 ] Nanoparticles coated with extracts from human lung epithelial type II or macrophage cells inhibited SARS‐CoV‐2 in a dose‐dependent fashion while nanoparticles coated with extracts from red blood cells were inactive (Figure 5e).…”
Section: Virus Particle Binding Inhibitorsmentioning
confidence: 99%